2020
DOI: 10.1177/1559325820923825
|View full text |Cite
|
Sign up to set email alerts
|

PRKCSH Alternative Splicing Involves in Silica-Induced Expression of Epithelial–Mesenchymal Transition Markers and Cell Proliferation

Abstract: Background: Mounting evidence suggests that alternative splicing is one of the ways for cells to adapt to environmental stress insults. The aim of this study was firstly to examine the effect of silica on the alternative splicing of lung fibrosis–associated genes. Methods: Microarray analysis was used to construct the alternative splicing profile. Functional experiments were conducted using Cell Counting Kit-8, cell cycle, apoptosis, and epithelial–mesenchymal transition (EMT) analyses. Alternative splicing va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…1 a). We harvested cells for transcriptomic detection based on our findings from our pilot study that suggested that cell damage at this timepoint could significantly induce EMT [ 29 31 ]. The details of the changes in mRNA expression are listed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 a). We harvested cells for transcriptomic detection based on our findings from our pilot study that suggested that cell damage at this timepoint could significantly induce EMT [ 29 31 ]. The details of the changes in mRNA expression are listed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…WB detection was conducted as previously reported [ 22 , 28 , 29 ]. In this study, antibodies against p53, E-cadherin, N-cadherin, and Vimentin were purchased from Cell Signaling Technology, Inc.(Danvers, MA, USA) and Abcam (Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%
“…WB detection was conducted as previously reported [22,28,29]. In this study, antibodies against p53, E-cadherin, N-cadherin, and vimentin were purchased from Cell Signaling Technology, Inc.(Danvers, MA, USA) and Abcam (Cambridge, UK).Images were captured and assessed using the ChemiDocXRS + system (Bio-Rad Laboratories).…”
Section: Cell Experimentsmentioning
confidence: 99%
“…1A). We harvested cells for transcriptomic detection based on our ndings from our pilot study that suggested that cell damage at this timepoint could signi cantly induce EMT [29][30][31]. The details of the changes in mRNA expression are listed in Table 1.…”
Section: De Ciency Of P53 Signi Cantly Alters Mrna Expression Followimentioning
confidence: 99%
“…13 We previously reported that PRKCSH expression increased in response to silica-induced epithelial–mesenchymal transition and that the knockdown (KD) of a PRKCSH-2 splice variant stimulated A549 cell proliferation by promoting epithelial–mesenchymal transition. 14 It remains unclear whether PRKCSH interacts with lung cancer immune infiltration-related signalling pathways and/or whether this affects lung cancer proliferation or prognosis.…”
Section: Introductionmentioning
confidence: 99%